EVALUASI PERATURAN BUPATI KUTA I KARTANEGARA NOMOR 36 TAHUN 2013 PENYELENGGARAAN ADMINISTRASI PENGUASAAN TANAH ATAS TANAH NEGARA DI KECAMATAN SAMBOJA - Usman Usman (Jurnal Paradigma (JP), 2022)
This study aims to determine the Evaluation of the Regulatory Policies of the Kutai Kartanegara Regent, Number 36 of 2013 concerning the Administration of State Land Tenure Administration in Samboja District and to determine the supporting and inhibiting factors for the Regulatory Policy of the Kutai Kartanegara Regent. This research is a qualitative descriptive research. . This research was conducted to emphasize the situation in order to find, understand, explain and obtain an overview of how the quality of public services is related to the problem under study. The research instrument is the researcher himself who acts as a data collection tool. Researchers as a research instrument aim to obtain valid and realistic data. The results of the study show that to improve the policy of the Kutai Kartanegara Regent Regulation number 36 of 2013, the government of Kutai Kartanegara Regency must provide the latest legal umbrella for the sub-district regarding the amount of fees charged to the community so that it becomes a collective agreement and the government should not stop socializing to the community. Related to the policy of the Regent of Kutai Kartanegara number 36 of 2013, it can be seen from several things such as: Effectiveness is a regulation that can regulate the community to understand their rights and obligations, Efficiency, this evaluation goes as expected, Adequacy based on the level of satisfaction in the community is very high and problems that arise with value differences do not occur in the field, and responsiveness based on the results of the assessment and data shows that if the policy is implemented. Keywords: Evaluation, Land Administration, Samboja Head Office